Coherent scattering cross sections of some rare earth compounds at small angles below 10° for 59.54 keV gamma rays. (January 2023) - Thulasi, P.V.; Joseph, Antony; Varier, K.M.; H.M., Somashekarappa; Kamat, Vinayak Anand; C.V., Vishnu
Abstract: The angle integrated total scattering cross sections of some rare earth oxides were determined experimentally for 59.54 keV gamma rays in the angular ranges of 0–4°, 0–6°, 0–8°and 0–10°. From the experimental total scattering cross sections, the corresponding angle integrated incoherent scattering cross sections obtained from ENDF library (based on the nonrelativistic Hartree–Fock form factor method) was subtracted to obtain the angle integrated coherent scattering cross sections. The angle integrated coherent scattering cross sections show good agreement with that determined from ENDF data. The effective atomic numbers of the selected rare earth oxides were extracted by applying the ratio of cross section method. The variation of angle integrated coherent scattering cross section with the effective atomic number of the selected compounds have been studied. Highlights: Study on coherent scattering of 59.54 keV gamma rays by some rare earth oxides. Comparison of results with cross sections derived from Evaluated Nuclear Data File. Extraction of effective atomic numbers by ratio of cross section method. Variation of coherent scattering cross section with effective atomic number.